Contagion of coronavirus disease—the first family cluster of Pakistan: a case series - Aisha Fareed Siddiqui; Nasir, Nosheen (Journal of the Pakistan Medical Association, 2023)
Coronavirus Disease has resulted in public health crisis all over the world. We describe the case series of a family, who travelled together to a mass gathering in Iraq, toured Syria, Lebanon, and Doha and returned to Karachi. The data describes the demographic and clinical features of these six members. There were three males and three females. One developed severe disease and died. Incubation period was between 8-14 days. Four patients were symptomatic, had diabetes mellitus and hypertension; and presented with fever. They also had bilateral airspace opacifications on chest X-ray. Our study describes familial clustering of SARS-CoV-2 and its person-to-person transmission. Keywords: Covid-19, Family cluster, Mass gathering, Epidemiological features.